A New Method of Fabrication for Multicolor Transparent Thin-film Solar Cell Module. Issue 1771 (2015) - Han, Meiying; Xie, Xishun; Chen, Yuan; Wu, Yabin; Zhong, Ming
ABSTRACT: In current transparent Si based photovoltaic (PV) module fabrication, green or infrared laser is the most common used band frequency to wipe off the silicon and back contact layer in perpendicular direction of cells. However, this method would result in more power loss than calculation value due to the side effects during the process such as constructional damage of module and shunt effect. A new method is presented here which focus on wiping off more silicon layer by employing green pulsed laser(532 nm wavelength) along the parallel direction of Pattern2, and it shows higher efficiency and more attractive appearance.